Ossifying Lipoma in Costal Arches That Suggest Extensive Pulmonary Involvement: Case Report - Angélica Tobón; Nhora M Silva; Mauricio Velásquez; Eliana Morales; Saveria Sangiovanni; Liliana Fernández-Trujillo (Clinical Pathology, 2020)
Background: Lipomas are the most common benign soft tissue tumors in the general population. These lesions can appear on any part of the body and usually develop in the subcutaneous superficial tissue. Lipomas that show ossifying changes are very rare, representing less than 1% of the reported lipomas. They usually manifest as hard nodular lesions in the head and neck, the extremities, the sternoclavicular region, and the subcutaneous tissue in general; they are rare in the costal arches. Case presentation: We report the case of a patient with a history of multiple diseases and 2 tumor-like lesions with internal lytic areas detected in the fourth right costal arch and in the eighth left costal arc; we describe his clinical manifestations, radiological and laboratory findings as well as the pathological results and outcome. Conclusions: Ossifying lipomas are rare benign tumors with asymptomatic clinical presentation. It is important to perform an adequate radiological differentiation from other more aggressive lesions such as liposarcomas.